2010
DOI: 10.1345/aph.1p141
|View full text |Cite
|
Sign up to set email alerts
|

Efavirenz Plasma Concentrations and Cytochrome 2B6 Polymorphisms

Abstract: Trough efavirenz concentrations were significantly higher in patients with the 785 (A to G) and 516 (G to T) variants. Midpoint efavirenz concentrations in Latinos were significantly higher than those of whites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
1
13
0
Order By: Relevance
“…Studies have reported an association between CYP2B6 genotypes and the pharmacokinetics of EFV and NVP in HIV‐infected patients of European and African ethnicities (Cabrera et al, ; Haas et al, ; Mahungu et al, ; Motsinger et al, ; Ribaudo et al, ; Rotger et al, ; Schipani et al, ; Wyen et al, ). Also, similar studies have been published in other ethnically diverse patients (Carr, Porte, Pirmohamed, Owen, & Cortes, ; Chen et al, ; Lindfelt, O'Brien, Song, Patel, & Winslow, ; Puthanakit, Tanpaiboon, Aurpibul, Cressey, & Sirisanthana, ; Ramachandran et al., ; To et al, ). In India, it is believed that we have different gene pools in south, north, east, and west regions.…”
Section: Introductionsupporting
confidence: 66%
“…Studies have reported an association between CYP2B6 genotypes and the pharmacokinetics of EFV and NVP in HIV‐infected patients of European and African ethnicities (Cabrera et al, ; Haas et al, ; Mahungu et al, ; Motsinger et al, ; Ribaudo et al, ; Rotger et al, ; Schipani et al, ; Wyen et al, ). Also, similar studies have been published in other ethnically diverse patients (Carr, Porte, Pirmohamed, Owen, & Cortes, ; Chen et al, ; Lindfelt, O'Brien, Song, Patel, & Winslow, ; Puthanakit, Tanpaiboon, Aurpibul, Cressey, & Sirisanthana, ; Ramachandran et al., ; To et al, ). In India, it is believed that we have different gene pools in south, north, east, and west regions.…”
Section: Introductionsupporting
confidence: 66%
“…To our knowledge, the association of c.516G Ն T with efavirenz pharmacokinetics is well established [26][27][28] but the impact of CYP2B6 haplotype, GAC (516G, 785A and g.21563C) on steady-state efavirenz plasma concentrations is not well-defined. It is unclear why the g.21563C>T polymorphisms, which are unlikely to impact on the functional effect of CYP2B6, were associated.…”
Section: Discussionmentioning
confidence: 97%
“…15 Plasma efavirenz concentrations may vary among patients based on a number of personal characteristics, such as genetics and weight. 15 Lindfelt et al 16 observed that Hispanics and Asians had increased concentrations of efavirenz and a higher rate of adverse drug reactions due to a possible polymorphism of CYP2B6.The investigators reported that the mean plasma efavirenz concentration at midpoint after a dose was 1.59 mg/ mL in Caucasians and 3.15 mg/mL in Hispanics.…”
Section: Discussionmentioning
confidence: 99%